Training and Assistance in Making Egg Hatching Machines to Increase the Independence of Poultry Farmers in Soropia Village Konawe Regency: Pelatihan dan Pendampingan Pembuatan Mesin Tetas Telur untuk Meningkatkan Kemandirian Peternak Unggas di Desa Soropia Kabuapten Konawe - Badaruddin, Rusli; Pagala, Muh. Amrullah; Nafiu, La Ode; Hakim, Muh Haidir; Kimestri, Asma Bio; Putri, Anindyaningrum Zainal; Ilahude, Meygi Caesarika Putri (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2025)
Community service activities carried out by the Faculty of Animal Husbandry lecturer team integrated with the Thematic KKN program from the Halu Oleo University Research and Community Service Institute (LPPM) Year 2024 were carried out in Soropia Village, Soropia District, Konawe Regency. Introducing the technique of making hatching machines and how to operate them to the community in Soropia Village. This is intended so that farmers can understand new technology in the poultry farming industry which functions to replace the role of mothers in incubating eggs and is expected to increase livestock productivity more optimally. Service activities in Soropia Village were carried out in two stages. The first stage was observation by conducting documentation data collection methods and discussions with community leaders as stakeholders. The results of the discussion showed that most of the community's understanding of egg incubators was still limited. The second stage involved developing a solution by designing and manufacturing a hatching machine, including procedures for its operation. The output achieved in this activity is an increase in insight and knowledge about automatic egg hatching machine technology.